Before we die. Season one [videorecording (DVD)] - Sharp, Lesley, 1964-; Gibson, Patrick, 1995-; Scroggs, Rebecca, 1982-; Gojanović, Toni; Turbiasz, Ryszard, 1953-; Knopfler, Issy; Pelka, Kazia, 1962-; O'Connor, John; Cvirn, Petar; Nayar, Nisha; Govaerts, Tijmen; Søkol, Rino; et al. (PBS, 2022)
Detective Hannah Laing becomes deeply conflicted when she discovers her son is playing a crucial role as an undercover informant in the investigation of a brutal murder.